Strategi Komunikasi Puskesmas Nagori Sayur Matinggi Dalam Mengajak Masyarakat Untuk Vaksinasi - Andrian, Rizky; Rasyid, Abdul; Zuhriah, Zuhriah (Journal of Computer Science and Information System(JCoInS), 2024)
This study is entitled communication strategy of Nagori Sayur Matinggi Health Center in inviting people to vaccinate. The purpose of this study was to determine whether the community received the vaccination message given by the Matinggi vegetable Health Center and the innovation applied by the Matinggi vegetable Health Center and whether it could be accepted by the community. This study uses a descriptive qualitative method using data collection techniques such as observation interviews and documentation, where in this study the subject of research is the Nagori Sayur Matinggi Health Center in inviting people to vaccinate. The focus of research in this study is how the Health Center invites the public to want the vaccine. The results of this study are Nagori Sayur Matinggi health center in their socialization explained several uses of vaccines, vaccines that can stimulate the immune system, reduce the risk of transmission, reduce the severe impact of the virus and they explained that the vaccine is safe for us because there are clinical trials and evidence. the Nagori Sayur Matinggi Health Center conducts innovations or ideas in disseminating the importance of vaccination to the community by door to door innovation.